LIMPAPEH DALAM KARYA TAPESTRI - Hilda Fauziah; Erwin Erwin (Serupa The Journal of Art Education, 2021)
The purpose of the creation of these final work to visualize the allusion to change Minangkabau women's culture in the form of an imperfect black butterfly into a wall decoration with a tapestri technique. The method in realization of these final work is through several stages of preparation, the stage of elaboration, the synthesis stage, the realization, concept and solution. The seven works that were visualized represent the title of the final work. So the translated work is entitled: 1) " Ensnared of The Times," 2) "Destructed of The Times" 3) "Irony", 4) "Ambiguous ", 5) "Imitation," 6) "Sarkasme," 7) "Slither ".Kata Kunci : Limpapeh, Kupu-kupu, Tapestri.